Pemerolehan Sintaksis Bahasa Minangkabau Pada Anak Usia 5 Tahun di Kambang - Marta, Melza; Emidar, Emidar; Nursaid, Nursaid (Universitas Negeri Padang, 2013)
There are three purposes of this study were to (1) describe the pattern of declarative Minangkabau language sentence for five years old children (2) describe the pattern of interogative Minangkabau language sentence for five years old children, and (3) describe the pattern of imperative Minangkabau language sentence for five years old children. Data were collected by using listening methods that are listening-speaking methods and free listening that included speaking. The subjects of this study were one person. Based on the result of study and explanation, it were concluded; The first, the pattern of declarative Minangkabau language sentence for five years old children were 10 pattern. Declarative sentence for five years old children consist of 1-9 spoken words. The second, the pattern of interrogative Minangkabau language sentence for five years old children were 5 pattern. Interrogative sentence for five years old children consist of 1-6 spoken words. The third, ,the pattern of imperative Minangkabau language sentence for five years old children were6 pattern. Imperative sentence for five years old children consist of 1-5 spoken words.